Efeito do ácido tânico sobre a toxicidade induzida pela 6-OHDA em células PC12, um modelo in vitro de doença de Parkinson - Alves, Amanda Aragão (2016)
Parkinson's disease (PD) is the second most common neurodegenerative disease in the elderly. It is characterized by progressive loss of dopaminergic neurons in the substantia nigra pars compacta, leading to a severe reduction in striatal dopamine content. The model using PC12 cells, a cell line of rat pheochromocytoma exposed to toxins that recapitulate different mechanisms of cell death in PD has been used as a screening test for neuroprotective agents. Among the principal mechanisms leading to cell death in neurodegenerative diseases including periodontal disease, inflammation, apoptosis and oxidative stress play an important role. The tannic acid (TA) is a polyphenol antioxidant effect of the chelator type and free radical scavenger. The aim of this study was to evaluate the possible effect of citoproteror AT cytotoxicity induced by 6-OHDA on PC12 cells. The cell morphology was evaluated using the fast Panotic color. Cell viability was assessed by the MTT test, cell death by propidium iodide by flow cytometry and ethidium bromide and acridine orange using optical microscopy. The determination of oxidative stress was done by measuring nitrite and nitrate and malondialdehyde. Apoptosis was assessed by evaluating the expression of caspases 3 and 7 and GSK-3β. Treatment with AT increased cell viability tests such as MTT, ethidium bromide / laraja acridine and membrane integrity by propidium iodide, retained cellular morphology, in addition to reducing the levels of nitrite and malondialdehyde, proving its antioxidant activity . Exposure of cells to the AT also decreased significantly the activation of effector caspases 3 and 7, resulting in a decrease in apoptosis. The results suggest that AT is a cytoprotective substance that can prevent the degeneration of dopaminergic neurons. However more studies must be done to prove the effects of the AT, so that it can be used therapeutically in PD.